Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Produktivitas Sebagai Variabel Intervening (CV. Dwi Tunggal Fauzi Sejahtera) - Mas’udah, Nia Arifiana; Arifin, Rois; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyze the effect of Work Motivation and Job Satisfaction on Employee Performance with Productivity as an Intervening Variable at CV. Dwi Tunggal Fauzi Sejahtera. This research employs a quantitative approach using a questionnaire-based data collection technique involving 67 respondents. The independent variables in this study are Work Motivation and Job Satisfaction, while the dependent variable is Employee Performance, with Productivity as the intervening variable. The research findings indicate that Work Motivation does not have a significant effect on Productivity. Job Satisfaction has a positive and significant effect on Employee Productivity. Work Motivation does not have a significant effect on Employee Performance. Job Satisfaction has a positive and significant effect on Employee Performance. Productivity does not have a significant effect on Employee Performance. Work Motivation does not have a significant effect on Employee Performance through Productivity. Job Satisfaction does not have a significant effect on Employee Performance through Productivity. Keywords: Work Motivation, Job Satisfaction, Productivity, Employee Performance